Analysis of Learning Curve in Robot-Assisted Radical Prostatectomy Performed by a Surgeon - Roman I. Slusarenco; Konstantin V. Mikheev; Artem O. Prostomolotov; Roman B. Sukhanov; Evgeny A. Bezrukov (Advances in Urology)
This study aimed to report the learning curve in robot-assisted radical prostatectomy (RARP) performed by one surgeon who is experienced in laparoscopic prostatectomies. The records of 145 RARP cases performed between 2015 and 2017 were evaluated retrospectively. Patients were divided into three groups: group 1 comprised the first 49 cases, group 2 comprised 50–88 cases, and the rest of the cases were assigned to group 3. Continence was defined as the necessity to use at least one pad during a day. Additionally, erectile function recovery was defined as having erection sufficient for sexual intercourse regardless of using a phosphodiesterase type 5 inhibitor. Continence and erectile function recovery were assessed during interviews at 3, 6, and 12 months after surgery. First, all procedures were successfully performed without conversions or blood transfusions. The median follow-up period was 22 months. Moreover, the median skin-to-skin operative time (OT) was 220 minutes. The median blood loss was 150 ml, and the mean hospital stay was 8.9 ± 3.87 days. The median prostate volume was 36 cm³. The overall positive surgical margin rate was 13.1%. Overall, 38 (26.2%) postoperative complications were observed, and 17.9% of them were graded as minor. Anastomotic leakage decreased significantly from group 1 to group 3 (26.5% and 7%, respectively). The continence recovery (0-1 pad) rates were 60.6%, 75.7%, and 84.9% at 3, 6, and 12 months after surgery, respectively. Subsequently, the erectile function recovery rates were 50.9% and 65.4% at 6 and 12 months after surgery, respectively. In conclusion, there are several types of learning curves for RARP. First, the shallowest learning curve was observed for the OT. Regarding the analysis of “advanced learning curve,” demonstrating the improvement of OT and blood loss is considered insufficient. Therefore, additional oncological and functional results that require a longer period of investigation are required.